Client satisfaction of maternity care in Lorestan province Iran - Farahnaz Changee; Alireza Irajpour; Masoumeh Simbar; Soheila Akbari (Wolters Kluwer Medknow Publications, 2015)
Background: Client satisfaction is an important indicator for assessment of the quality of care provided. Detecting patients dissatisfaction and trying to find the most effective and costly services is the basic way for improvement of service quality. The purpose of this study was to determine the satisfaction level of women in the maternity care centers (hospitals) of Lorestan University of Medical Sciences, Iran. Materials and Methods: In this descriptive cross-sectional study, the satisfaction level of 200 patients who received care during childbirth in province hospitals was assessed using a researcher-made questionnaire. Women in maternity care units completed the questionnaires. Results: The mean maternity care satisfaction score was 66.6 ± 3.5. The lowest satisfaction level was related to getting to know the delivery room (64%) and vaginal examination (66%). The highest satisfaction score was related to confidentiality of the information (86%) and trusting the midwife (84%). Regarding the environmental factors, the lowest satisfaction was related to respecting silence in the pain room (69.5%) and the highest was related to cleanliness and hygiene of the delivery room (84%). Conclusions: Our results suggest the relative satisfaction of women receiving care in the health centers of Lorestan province; but this level of satisfaction does not mean that the delivery of care in this province is perfect. By reviewing the policies and the existing care programs regarding promoting the quality of services, managers can increase clients' satisfaction.